Need of an Ancient Roots to Modern Medicine in the Treatment of Cancer- A review - Manish Gunjan,; Jegathambigai Rameshwar Naidu,; Roy Rillera Marzo,; Nabil Saad Mohammed Harmal, (International Journal of Phytomedicine, 2017)
The already available expensive conventional therapies for cancer like chemotherapy and radiotherapy have a number of side effects such as myelosuppression and neurological, cardiac, pulmonary, and renal toxicity, which pose serious harm to the quality of life. Therefore, there is a need to develop treatment options that include more potent and less toxic anticancer drugs as compared to existing drugs. Studies have shown that regular consumption of fruits and vegetables because of phytochemical compounds extracted from them inhibiting the activity of antioxidant and free radicals which in turn showing anti-cancer activities. More recent semi-synthetic analogues of these agents are vinorelbine (VRLB) and vindesine (VDS). These agents are primarily used in combination with other cancer chemotherapeutic drugs for the treatment of a variety of cancers. VLB is used for the treatment of leukaemia, lymphomas, advanced testicular cancer, breast and lung cancers, and Kaposi’s sarcoma, and VCR, in addition to the treatment of lymphomas, also shows efficacy against leukaemia, particularly acute lymphocytic leukaemia in childhood. VRLB has shown activity against non-small-cell lung cancer and advanced breast cancer. Therefore there is need of developing cell cycle-based, mechanism-targeted ancient based modern cancer therapies that emulate the body's natural process in order to stop the growth of cancer cells. This approach can limit the damage to normal cells and the accompanying side effects caused by conventional chemotherapeutic agents. This review focuses on the role of ancient medicine in modern research and anticancer drug development. The current findings and known anticancer agents from natural sources are discussed, and recent therapeutic advances in this field are presented.